2020
DOI: 10.1177/0907568220965660
|View full text |Cite
|
Sign up to set email alerts
|

Enacting sabotage in siblings’ conflicts: Desired objects and deceptive bodies

Abstract: The present study examines sibling’ conflict trajectories with a specific focus on acts of sabotage – deliberate obstruction or destruction of activities with an object. Multimodal interaction analysis is used to understand how siblings’ conflicts are organised through multiple (verbal and embodied) practices. We further draw on childhood studies that focuses on children’s material practices and use the term enactment to better understand human-nonhuman relations. The study found that children put considerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…This time the tomato is frozen in its trajectory towards the milk, hovering just above the surface, and is combined with a mischievous gaze towards dad, an “O”‐like shape of the mouth and raised eyebrows (line 8, Figure 2.1). Clearly, Gustav's ‘body configuration’ (Zotevska et al, 2020) indicates that he is staging a rule violation. When dad repeats his reprimand of the possible ‘bathing’ activity (line 9), Gustav retracts the tomato and smiles (line 10), appearing amused.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This time the tomato is frozen in its trajectory towards the milk, hovering just above the surface, and is combined with a mischievous gaze towards dad, an “O”‐like shape of the mouth and raised eyebrows (line 8, Figure 2.1). Clearly, Gustav's ‘body configuration’ (Zotevska et al, 2020) indicates that he is staging a rule violation. When dad repeats his reprimand of the possible ‘bathing’ activity (line 9), Gustav retracts the tomato and smiles (line 10), appearing amused.…”
Section: Resultsmentioning
confidence: 99%
“…Since recent conceptualizations of materiality in childhood studies have been largely theoretical (Esser, 2017), there is a call to further study children's material practices. Some studies have had such an explicit focus and found that everyday things, for example school bags (Dannesboe, 2019), socks (Orrmalm, 2020), rooms (Palludan & Wentzel Winther, 2017) and tools (Zotevska et al, 2020) were central actors in the everyday lives and relations of children and families. For instance, Rautio and Jokinen's (2016) study on children's engagements with a snow pile argues for focusing on activities with things that 'matter'.…”
Section: Everyday Things In Childhood Studiesmentioning
confidence: 99%
“…Social constructionism overall prevails in Child Studies, but there are exceptions where the notion of enactment is used (e.g. including but not limited to Eßer, 2017;Eßer et al, 2016;Lindgren et al, 2014;Samuelsson et al, 2015;Sparrman, 2014Sparrman, , 2015aSparrman, , 2020Sparrman & Sandin, 2012;Sparrman et al, 2016;Spyrou, 2019;Zotevska et al, 2021). "Social construction" refers to practices resulting in "durable realities" (Woolgar & Lezaun, 2015), whereas "enactment" emphasizes that these realities are precarious.…”
Section: Values In Practicementioning
confidence: 99%